Investigation of gravity waves using horizontally resolved radial velocity measurements - Stober, G.; Sommer, S.; Rapp, Markus; Latteck, R. (Atmospheric Measurement Techniques, 2013)
The Middle Atmosphere Alomar Radar System (MAARSY) on the island of Andøya in Northern Norway (69.3 N, 16.0 E) observes polar mesospheric summer echoes (PMSE). These echoes are used as tracers of atmospheric dynamics to investigate the horizontal wind variability at high temporal and spatial resolution. MAARSY has the capability of pulse-to-pulse beam steering allowing for systematic scanning experiments to study the horizontal structure of the backscatterers as well as to measure the radial velocities for each beam direction. Here we present a method to retrieve gravity wave parameters from these horizontally resolved radial wind variations by applying velocity azimuth display and volume velocity processing. Based on the observations a detailed comparison of the two wind analysis techniques is carried out in order to determine the zonal and meridional wind as well as to measure first-order inhomogeneities. Further, we demonstrate the possibility to resolve the horizontal wave properties, e.g., horizontal wavelength, phase velocity and propagation direction. The robustness of the estimated gravity wave parameters is tested by a simple atmospheric model.